2007
DOI: 10.1002/bsl.769
|View full text |Cite
|
Sign up to set email alerts
|

Criminality and continued DUI offense: criminal typologies and recidivism among repeat offenders

Abstract: We examined over 20,000 arraignment records to define criminal typologies and post-treatment driving under the influence of alcohol (DUI) convictions for a select cohort of 1,281 repeat DUI offenders who were offered and elected treatment as an alternative to incarceration; we compared this information with a similar data analysis collected 20 years previously. Analyses of 8,600 prior-to-treatment convictions defined four basic crime profiles: only DUI and other substance-related offenses (60%), plus crimes ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 16 publications
4
30
1
Order By: Relevance
“…Another possible assumption is that, as older age tends to be related to higher family income and financial independence, the application of fines may not have the necessary impact to prevent drinking and driving behaviors in this population (there is not an actual financial burden on the recidivist). Also, the recurrence rate of DUI violations found in our study was lower than the rates reported in other international studies, 13 probably as a result of a poor enforcement of traffic laws in Brazil; this scenario generates a sense of impunity among drivers and thus contributes to maintaining the delinquent behavior. 27 Once again, this finding underscores the need to enforce stricter laws, with mass media campaigns and news coverage to help reduce the widespread perception of impunity after drinking and driving.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Another possible assumption is that, as older age tends to be related to higher family income and financial independence, the application of fines may not have the necessary impact to prevent drinking and driving behaviors in this population (there is not an actual financial burden on the recidivist). Also, the recurrence rate of DUI violations found in our study was lower than the rates reported in other international studies, 13 probably as a result of a poor enforcement of traffic laws in Brazil; this scenario generates a sense of impunity among drivers and thus contributes to maintaining the delinquent behavior. 27 Once again, this finding underscores the need to enforce stricter laws, with mass media campaigns and news coverage to help reduce the widespread perception of impunity after drinking and driving.…”
Section: Discussioncontrasting
confidence: 84%
“…In the U.S., treatment of DUI offenders has achieved satisfactory results. 13 This study presented limitations in the generalization of findings due to the study period and because it referred to only one state in Brazil. Moreover, it was not possible to identify the psychiatric comorbidities present in the sample, which could have altered results.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, some studies indicate that the likelihood of drunk driving recidivism increases with increasing BAC at the time of arrest (e.g., Armstrong et al, 2014;C'de Baca et al, 2001), whereas other studies do not find that effect (e.g., Cavaiola et al, 2007). Other factors related to recidivism include drinking frequency (Schell et al, 2006), use of prescription drugs (Dickson et al, 2013), a criminal record (LaBrie et al, 2007), neurocognitive impairment (Ouimet et al, 2007), and age and education level (C'de Baca et al, 2001). Also gender plays a role, as drunk driving recidivism is more prevalent among male drivers than female drivers (Armstrong et al, 2014;C'de Baca et al, 2001;Lapham et al, 2000).…”
Section: Introductionmentioning
confidence: 94%
“…Motivational interviewing (MI; Miller, 2004) is currently the object of intense interest as a psychosocial intervention to effectively and expeditiously intervene in alcoholism and other problems, populations, and settings (Chanut, Brown, & Dongier, 2005;Dunn, Deroo, & Rivara, 2001;Hettema, Steele, & Miller, 2005;Knight, McGowan, Dickens, & Bundy, 2006;Lundahl & Burke, 2009;Rubak, Sandbaek, Skipper, Hunt, & Chang, 2000), treatment refractoriness (LaBrie, Kidman, Albanese, Peller, & Shaffer, 2007;WellsParker, Anderson, Landrum, & Snow, 1988;Wells-Parker, Bangert-Drowns, McMillen, & Williams, 1995), poor problem recognition, and resistance to intervention participation Nochajski & Stasiewicz, 2005;Voas, Tippetts, & McKnight, 2010). Hence, MI seems well suited for intervening with DWI recidivists.…”
Section: Introductionmentioning
confidence: 97%